Temporal Gut Microbial Changes Predict RecurrentClostridiodes DifficileInfection in Patients With and Without Ulcerative Colitis. Issue 11 (November 2020) - Lee, Allen A.; Rao, Krishna; Limsrivilai, Julajak; Gillilland, Merritt; Malamet, Benjamin; Briggs, Emily; Young, Vincent B.; Higgins, Peter D. R.
Abstract : Background: : Ulcerative colitis (UC) carries an increased risk of primary and recurrent Clostridiodes difficile infection (rCDI), and CDI is associated with UC flares. We hypothesized that specific fecal microbial changes associate with UC flare and rCDI. Methods: : We conducted a prospective observational cohort study of 57 patients with UC and CDI, CDI only, and UC only. Stool samples were collected at baseline, at the end of antibiotic therapy, and after reconstitution for 16S rRNA sequencing. The primary outcomes were recurrent UC flare and rCDI. Logistic regression and Lasso models were constructed for analysis. Results: : There were 21 (45.7%) patients with rCDI, whereas 11 (34.4%) developed UC flare. Patients with rCDI demonstrated significant interindividual ( P = 0.008) and intraindividual differences ( P = 0.004) in community structure by Jensen‐Shannon distance (JSD) compared with non‐rCDI. Two cross‐validated Lasso regression models predicted risk of rCDI: a baseline model with female gender, hospitalization for UC in the past year, increased Ruminococcaceae and Verrucomicrobia, and decreased Eubacteriaceae, Enterobacteriaceae, Lachnospiraceae, and Veillonellaceae (AuROC, 0.94); and a model 14 days after completion of antibiotics with female gender, increased Shannon diversity, Ruminococcaceae and Enterobacteriaceae, and decreased community richness and Faecalibacterium (AuROC, 0.9). Adding JSD between baseline and post‐treatment samples to the latter model improved fit (AuROC, 0.94). A baseline model including UC hospitalization in the past year and increased Bacteroidetes was associated with increased risk for UC flare (AuROC, 0.88). Conclusion: : Fecal microbial features at baseline and after therapy predict rCDI risk in patients with and without UC. These results may help risk stratify patients to guide management.